2010
DOI: 10.1186/1471-2393-10-32
|View full text |Cite
|
Sign up to set email alerts
|

Policies for care during the third stage of labour: a survey of maternity units in Syria

Abstract: BackgroundCare for women during the third stage aims to reduce the risk of major haemorrhage, but is very variable. The current World Health Organisation (WHO) recommendation is that care should include administration of a uterotonic (oxytocin, if it is available) soon after birth of the baby, delayed cord clamping, and delivery of the placenta by controlled cord traction.MethodsTo ascertain care policies used during the third stage of labour in maternity units in Syria, we conducted a survey of 69 maternity u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Despite these limitations, no uniformity in the management of the third stage of labor was found, a finding common in other studies [34][35][36] . Even though the study was not a mixed-methods study, some samples of citations were included in order to provide a useful supplement to the descriptive data.…”
Section: Strengths and Limitationsmentioning
confidence: 89%
“…Despite these limitations, no uniformity in the management of the third stage of labor was found, a finding common in other studies [34][35][36] . Even though the study was not a mixed-methods study, some samples of citations were included in order to provide a useful supplement to the descriptive data.…”
Section: Strengths and Limitationsmentioning
confidence: 89%
“…A total of 30 articles were identified that provided description relating to maternity health professionals' knowledge, attitudes, or practice of umbilical cord clamping. Twelve papers were excluded because they did not meet inclusion criteria or the aims of this integrative review 20–31 . One short report of original research findings that provided minimal yet sufficient methodological detail 32 was also included because the study aims and results were directly relevant to this review.…”
Section: Aims and Methodsmentioning
confidence: 99%
“…Twelve papers were excluded because they did not meet inclusion criteria or the aims of this integrative review. 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 One short report of original research findings that provided minimal yet sufficient methodological detail 32 was also included because the study aims and results were directly relevant to this review. Analysis of eligible studies identified four main subject areas through a constant comparison method; an overarching approach in the development of the results in IRs.…”
Section: Aims and Methodsmentioning
confidence: 99%
“…The development of the device was informed by the best practice reviews that recommend delayed cord clamping at birth [ 23 , 24 , 25 ], the experience of using the LifeStart trolley in the United Kingdom [ 14 , 15 ], and recommendations for promoting delayed cord clamping for transition at birth [ 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%